Green governance and institutional resilience: strengthening environmental policies for a low-carbon economy in mangrove ecosystems - Nasution, Mimin Sundari; Rusli, Zaili; Heriyanto, Meyzi; Zulkarnaini; Syahza, Almasdi; Adianto; Mayarni; Ismandianto (Frontiers in Political Science, 2025)
IntroductionThis study addresses a significant empirical gap by examining how institutional resilience mediates the relationship between green governance and environmental policy effectiveness in managing mangrove ecosystems in Indonesia.MethodsA mixed-methods design was employed, integrating Structural Equation Modeling (SEM) and MICMAC analysis to investigate causal relationships and strategic interdependencies.ResultsSEM results indicate that green governance exerts a significant influence on institutional resilience (β = 0.67), environmental policy effectiveness (β = 0.61), and the low-carbon economy (β = 0.52), with institutional resilience and policy effectiveness serving as key mediating variables (Sobel z = 5.98 and 5.47, respectively). MICMAC analysis identifies public participation, regulatory enforcement, and environmental economic instruments as primary driving variables with high influence and low dependency. Institutional resilience emerges as a critical linkage factor, reflecting its dual function in both shaping and being shaped by governance dynamics.DiscussionThe study offers theoretical, methodological, and practical contributions. Theoretically, it elucidates the mediating role of institutional resilience in connecting green governance to policy effectiveness and the transition toward a low-carbon economy. Methodologically, it integrates SEM and MICMAC analysis, combining statistical rigor with strategic foresight. Contextually, it provides empirical insights from mangrove ecosystems in Indonesia, representing the Global South, where governance challenges remain pressing and underexplored. Practically, the findings highlight actionable priorities—such as public participation, regulatory enforcement, and economic instruments—offering evidence-based policy direction to strengthen institutional resilience and advance green governance toward a low-carbon transition.